Effects of including endurance and speed sessions within small-sided soccer games periodization on physical fitness - Castillo, Daniel; Raya-González, Javier; Sarmento, Hugo; Clemente, Filipe; Yanci, Javier (Biology of Sport, 2021)
The main aim of this study was to analyse the effects of including additional speed and endurance sessions during small-sided games (SSG) training periodization on physical fitness in professional soccer players. Sixteen outfield players (age = 25.6 ± 7.6 years) who competed in the First Division of a European League participated in this study. Players were randomly assigned to perform only the SSG periodization (G-SSG group) or to add endurance and speed training contents to the SSG (ES-SSG group). Before and after the 6-week experimental period, a Yo-Yo Intermittent Recovery Test level 1 (YYIR1) and a 40 m sprinting test were performed. Rating of perceived exertion (RPE) was also measured after each training session. The G-SSG group showed a large improvement in the YYIR1 performance (p = 0.018–0.028; ES = 0.521–0.576) after the training programme, whereas no significant changes were observed for the ES-SSG group (p = 0.763–1.000; ES = 0.000–0.014). In addition, no significant differences (p > 0.05, ES = 0.005–361, trivial to small) in sprint performance at 5 and 10 m intervals up to 40 m were observed at post-training in comparison to pre-training evaluation in G-SSG and ES-SSG groups. No significant differences (p > 0.05) between groups were observed at baseline in the YYIR1 test. The 6-week SSG training supported with only six endurance and speed training sessions was no more effective than well-organized SSG alone for improving running endurance in professional soccer players.